THE PROBLEM OF ACTIVATING COGNITIVE ACTIVITY STUDENTS IN THE STUDY OF GEOGRAPHY (Pedagogy of Higher and Secondary Education, 2008)
In article problems of studying of cognitive activity of students and learning senior classes are considered at studying economic geography. Concepts cognitive activity and cognitive interest in the pedagogical literature are considered.